1996
DOI: 10.1007/bf00188525
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic treatment of a sigmoid perforation after colonoscopy

Abstract: The authors report a case of sigmoid colon perforation post colonoscopic polypectomy. Such perforation is rare and has been estimated to occur between 0.1 and 3% of the time. Surgical treatment is necessary when there is deterioration of the clinical state. In this reported case, surgical closure of the perforation was achieved by laparoscopy. We believe that this approach is effective for colonic suture, peritoneal lavage, and drainage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 14 publications
0
7
0
1
Order By: Relevance
“…The traditional approach was a laparotomy with either primary repair or diverting colostomy. There have been several reports of laparoscopic repair of perforations after colonoscopy in adults [1][2][3][4][5][6][7][8][9][10][11][12] and some reports of nonoperative management [13][14][15]. We present 2 children with colonic perforation after colonoscopic polypectomy who were treated successfully by laparoscopy.…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…The traditional approach was a laparotomy with either primary repair or diverting colostomy. There have been several reports of laparoscopic repair of perforations after colonoscopy in adults [1][2][3][4][5][6][7][8][9][10][11][12] and some reports of nonoperative management [13][14][15]. We present 2 children with colonic perforation after colonoscopic polypectomy who were treated successfully by laparoscopy.…”
mentioning
confidence: 75%
“…Although patients with mild symptoms and negative imaging studies could be observed, any clinical suspicion of a perforation is sufficient to justify a low threshold for operative intervention. There are several reports of successful laparoscopic repair of colon perforation after colonoscopy in adults [1][2][3][4][5][6][7][8][9][10][11][12]. Each recommends an approach consistent with traditional surgical principles such as adequate visualization, control of spillage, incorporating viable tissue in the repair, and broad-spectrum antibiotics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some case reports indicate that laparoscopic treatment of colonic perforations has been performed by suture or tangential resection. However, the two case reports of simple closure by suture do not mention about thermal damage or necrosis [6,11,12]. We would like to draw the reader's attention to the issue of thermal damage, since it can cause rupture of the suture line as well as necrosis.…”
Section: Discussionmentioning
confidence: 95%
“…So finden sich in der Literatur zunehmend Kasuistiken über laparoskopisch assistierte Eingriffe, Wedge-Resektionen und laparoskopische Übernä-hungen [1,2,7,10,14,15,16,20,21,22].…”
Section: Diskussionunclassified